Enterobacteriaceae, cronobacter(enterobacter) sakazakii and microbial population in infant formula products in the Malaysian market - Norrakiah Abdullah Sani; Lim, Yen Yi (Universiti Kebangsaan Malaysia, 2011)
This study was carried out to detect and identify the presence of Enterobacteriaceae, and Cronobacter sakazakii, and determine the microbial population of infant formula products obtained from hypermarkets and a private hospital in Malaysia. Sixteen infant formulas and 14 special infant formulas from eight manufacturers were tested. Enterobacter cloacae, E. asburiae, Klebsiella pneumoniae spp. pneumoniae, K. planticola and Pantoea sp., 3 were confirmed present in five samples using ID 32E biochemical test (Biomerieux). C. sakazakii was not detected in any of the infant formulas tested. Five samples failed to comply with the microbiological criterion for aerobic plate count. The infant formula and special infant formula samples with different ingredients and nutrient composition did not show any significant difference in terms of aerobic plate count. Although one of the samples contained probiotic, the high microbial count for the other samples could have been contributed by the above identified Enterobacteriaceae since the infant formula samples non-sterile and contamination could have occurred during milk production and/ or milk preparation. It is imperative to prepare the infant formula milk samples according to the manufacturer’s instruction and in an aseptic condition.